Modeling and Characterization of 10-kV SiC MOSFET Modules for Medium-Voltage Distribution Systems - Oggier, German Gustavo (2020)
This work presents the modeling and characterization of 10-kV SiC MOSFET modules used for medium-voltage distribution system applications. In addition to the nonlinear junction capacitances of the devices, the model includes the nonlinearities present at steady-state like transfer characteristics and the behavior in the Ohmic region, which allows to increase the accuracy of the SiC MOSFET model. Furthermore, the parasitic inductances in the circuit (such as the source inductance shared by the power stage and driver loop and the drain inductance) are considered in the model since it has been demonstrated previously that it influences the total losses. By using the proposed model, the calculated voltage and current transients show a good match with the experimental results.